Pengembangan Sistem Informasi Berbasis Mikrokontroler untuk Otomasi dan Pemantauan dalam Berbagai Aplikasi - Juniar Hadianti (STIKes Ibnu Sina Ajibarang, 2025)
Microcontroller-based information systems play a crucial role in enhancing the efficiency and effectiveness of various automation and monitoring applications. However, many manual processes across different fields require time and are prone to errors. This study aims to develop a microcontroller-based information system to automate real-time data collection and monitoring in various applications, such as industry, environment, and smart homes. The method used involved the development of a prototype system designed to integrate sensors and microcontrollers in data processing and automated decision-making. The results showed that this system significantly improved the efficiency, accuracy, and speed of data processing while minimizing human intervention. In conclusion, microcontroller-based information systems offer innovative solutions that can be widely applied across various fields to enhance performance and service quality.